Peta Global Isu Riset Pendidikan Agama: Studi Bibliometrics Pada Database Scopus Tahun 2000-2021 - Hasan Albana; Nurul Qolbi Izazy; Nursalamah Siagian; Hayadin (Badan Litbang dan Diklat Kementerian Agama RI, 2023)
This study aimed to explore the general trends of religious education through a literatures review analysis. This study uses a bibliometric method by utilizing data from the Scopus database from 2000 to 2021 and visualizing it using VOSviewer. The study found 1,372 published articles from 133 countries focused on religious education. From these results, the most influential article is entitled 'Worldview: The Meaning of the Concept and the Impact on Religious Education' written by Van Der Kooij J.C. In addition, an influential author is Wright A., who has authored 16 studies and obtained 187 citations. In comparison, the most influential country is the United Kingdom, which has published 347 studies and received 2234 citations. Based on the identification of keywords, this study shows that most religious education research areas cover curriculum, spirituality, Islamic religious education, secularism, and schools. Meanwhile, studies on inter-culturalism, sexuality, trauma-informed pedagogy and healing, moral disengagement, science, adolescent mental health, conflict of values, borderlands, democratic state, and digital literacy concerning religious education were still little discussed. Therefore, this study is expected to provide an overview of the research carried out and directions for further research in studying religious education.